Soil water isotopes from West Africa (Benin and Senegal) - Anne Alexandre (PANGAEA, 2025)
Isotopic composition of soil water extracted by centrifugation and analyzed by Cavity Ring Dow Spectroscopy (CRDS) from 10 soil cores collected at Belefoungou (BE, Benin), Nalohou (NA, Benin) and Dahra (DA, Senegal). For comparison, the isotopic composition of precipitation preceding the samplings are shown.
In: Alexandre, A (2025): Climate and triple oxygen isotope of precipitation, groundwater, soil water, plant water, and phytolith data from West Africa (Benin and Senegal) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984133